Integration of Local Wisdom in the Conservation of Seaweed (Kappaphycus alvarezii) in Tanjung Village, Pamekasan, Madura - Wulandari, Siska Ayu; Isdiantoni (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
Seaweed cultivation (Kappaphycus alvarezii) is the primary source of livelihood for the coastal communities of Tanjung Village, Pamekasan, Madura. This study aims to examine the role of local wisdom in seaweed conservation, including traditional practices that support the coastal ecosystem. The research employed a qualitative approach using semi-structured interviews conducted with 15 key informants, including seaweed farmers, traditional leaders, and village officials. This was followed by a Focus Group Discussion (FGD) with 10 participants from seaweed farmer groups to confirm data and collectively discuss conservation and local wisdom issues. The collected data were analyzed using thematic analysis techniques to establish the relationship between traditional practices and the sustainability of seaweed. The study indicates that the local wisdom practiced by the Tanjung Village community, such as sasi rules (a traditional prohibition system) and traditional planting methods, contributes significantly to the conservation of Kappaphycus alvarezii seaweed. This local wisdom not only preserves the availability of seaweed resources but also strengthens social cohesion within the community. The integration of local wisdom with modern technology has the potential to enhance the effectiveness of conservation and seaweed productivity. Recommendations for advancing the cultivation of Kappaphycus alvarezii in Tanjung Village include: Collaboration between modern science and traditional practices is necessary to develop environmentally friendly and productive cultivation techniques, and the development of a community-based conservation model involving traditional leaders, farmers, and village officials is crucial for sustainable seaweed resource management.